Pemberdayaan Usaha Mikro: Optimalisasi Kebutuhan Modal Umkm Melalui Dukungan Program Sekolah Wirausaha ‘Aisyiyah - Nurul Aisah; Dewangga Eka Syahputra (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to increase the understanding of MSME players in calculating business capital needs. The service partners were MSMEs from the 'Aisyiyah (PDA) Karanganyar Regional Leaders who were attended by 52 participants. A common problem faced by partners is that partners do not understand how to calculate business capital correctly. This service is focused on assisting partners so they can calculate business capital needs to improve the quality of their business. The methods used in this service are preparation, socialization of material and training in calculating business capital. From the results of the activity, it was found that the participants experienced an increase in their understanding of business capital and how to calculate it correctly and found solutions to the problems they faced.